Establishing Islam in Sweden: The First Tatar Community and Muslim Congregation and Their Sources - Sorgenfrei, Simon (Studia Orientalia Electronica, 2020)
This article focuses on the history and establishment of the first Muslim congregation and organisation in Sweden, Turk-Islam Föreningen i Sverige för Religion och Kultur (Turk-Islamic Association for Religion and Culture), which was founded in the late 1940s by a small group of immigrants and refugees of Tatar and Turkish origin. The community has been the object of earlier research (see Svanberg & Westerlund 1999; Ståhlberg & Svanberg 2016; Sorgenfrei 2018) but the following is a first attempt to describe the historical background of the Tatars in Sweden through systematic archival work. The article thus aims at being also an orientation to the archival and private sources of the group and their organization and to point out some topics of interest for further research.